Yield losses caused by powdery mildew on bread wheat cultivars under irrigated Mediterranean conditions in Spain - Briceño-Felix G.; Huerta-Espino J.; Torres i Ruiz L.; Betbese J.A.; Martín Sánchez J.A. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
The aim of this work was to determine the effects of powdery mildew severity on grain yield reductions in several bread wheat cultivars that varied in resistance to this fungus under irrigated Mediterranean conditions in Spain. Field experiment was carried out at Gimenells, province of Lerida, Spain, during 2005-2006 growing season under natural infections of powdery mildew. Field design was a randomized complete block in a split-plot arrangement of treatments, with three replications. Bread wheat cultivars were allocated to the main plots and fungicide treatment to the subplots. Untreated plots were compared with treated plots kept nearly diseased-free with four foliar applications of two alternated fungicides: cyproconazole 10 percent p/p (800 g/ha) and metal-tiofanato 45 percent p/v (0.675 l/ha). Powdery mildew severities were determined by estimating the percentages of leaf area infected on the whole plot and the upper three leaves of each cultivar. Disease assessments were made at Zadoks growth stages (GS): GS-24, GS-32, GS-43, GS-57, GS-61, GS-71 and GS-76. Disease severity assessments were used to calculate the area under the mildew progress curve (AUMPC). No other foliage disease was observed during the study. The estimation of yield loss, based on disease severity was obtained by a linear model of second grade.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)